Post-1979 Iran: Anti-colonialism and legacies of Euro-American spaces and temporalities - Ram, Haggai (Hagar: Studies in Society and Culture, 2010)
The argument I put forth rests on an ostensibly simple and straightforward idea: the 1979 Islamic Revolution in Iran did not serve as an epistemic or epochal break in Iranian history. By viewing pre- and post-1979 Iran as mutually constitutive parts of a continuing history, and tracing the dynamic of the Islamic Republic of Iran’s ongoing dialogue and engagement with Western representational practices, I show how Iran’s current clerical leaders sought to reinterpret, appropriate, deflect and resist Eurocentric notions and constructions and, in doing so, also give them new meanings. The fact that Iran’s representational strategies remain wedded to, and embedded in, Eurocentric discursive formations and subjectifications, I argue, is perhaps another testimony to the 1979 revolution’s failure to live up to its decolonizing emancipatory vision. This predicament, no doubt, is common to many other postcolonial projects. However, the Iranian case is perhaps more intriguing, because the Islamic Republic of Iran is currently posited as the West’s quintessential "other."